Best Practice Kepemimpinan Suster dalam Meningkatkan Nilai Akreditasi Sekolah di SDK Cor Jesu Malang - Mokhamad Yaurizqika Hadi; Mukti Sari Utami; Ahmad Yusuf Sobri (Universitas Indraprasta PGRI Jakarta, 2022)
The problematic results of school accreditation have not described the objective condition of the school. The results of accreditation have not shown indicators of accountability and have not been used as a school development tool so a leader who has the sufficient intellectual ability is needed to be able to work from the level of vision to its implementation. This study aims to find out the best practices of Nuns leadership in improving accreditation at SDK Cor Jesu Malang. Researchers used a case study approach and data collection was carried out by direct observation, in-depth interviews, and documentation in March 2022. Researchers were present to collect data, process data, and check the validity of the data obtained. The data analysis technique used were data collection and reduction as well as a conclusion. The results of this study: 1) To increase accreditation at SDK Cor Jesu Malang, Nuns has a plan or program which is then implemented by all teachers according to their duties and responsibilities. 2) School accreditation can increase if teachers, administrative staff, and students are properly empowered to master the duties of the school principal, teachers, administrative staff, and students and can then carry out an in-depth evaluation. 3) The program created must be socialized to get support from all school stakeholders. 4) The commitment of all stakeholders is an important factor in achieving increased accreditation in schools.